Bottom-up perspective of leadership in sports: Examining the requirements of athletes on their trainers` competence - Ramesberger, R. (International Journal of Sports Science, 2022)
The purpose of this study is to examine the bottom-up perspective of athletes in competitive sports concerning their competence requirements on their trainers. Competitive athletes (N = 138) from the regional team level up to the national team level (in individual and team sports) rated within a questionnaire their own requirements, wishes and perceptions on their trainers behaviours and competences. The gathered data is analysed using SPSS 28 and AMOS 28. The results revealed that there are moderate correlations between certain leadership competences and the followers` engagement. They indicated that the "Knowing-Being-Doing" of trainers is relevant for their acceptance by the athletes. "Being" revealed to be the most decisive factor. Furthermore, the trainers` visions revealed to be a perceived lack by the followers. As a conclusion the leader-centred top-down approaches are not that suitable and, furthermore, the holistic personality of the trainer is decisive for his acceptance. The findings highlight practical implications for competence development of sports